Assessment of the agro-industrial sugar yield of sugar mills in Mexico - Altamirano-Cárdenas, J Reyes; Sandoval-Romero, Fermín; Cuevas-Alvarado, Cristóbal Martín; Montiel-Batalla, Blanca Margarita (Revista Mexicana de Ciencias Agrícolas, 2025)
In Mexico, sugarcane is important to guarantee the food sufficiency of standard sugar. This work aimed to evaluate the technical inefficiency of the agro-industrial sugar yield of the sugar mills in Mexico for the 2022-2023 harvest in order to identify the most inefficient sugarcane production units. The model used was the stochastic frontier analysis approach. The results showed that, of the 39 mills analyzed, a group of six mills showed the lowest performance in their agro-industrial yield of standard sugar indicator in the study harvest. These sugar mills and their respective efficiency were Puga (89.3%), Alianza Popular (88.9%), Plan de San Luis (88.5%), Plan de Ayala (88.3%), Progreso (85.6%), and El Mante (84.9%). The technical inefficiency of these six production units is greater than 10% and is due to inadequate management and poor production practices and not to random variables such as the climate. The main conclusion of the research is that 88.3% of the relative technical inefficiency in the agro-industrial yield of sugar per unit area is attributable to causes of the internal environment of such companies and only 11.7% to random factors outside the sugar mills.